A thermo-metallurgical-mechanical model for selective laser melting of Ti6Al4V - Li, Biao (2019)
A thermo-metallurgical-mechanical coupling model is developed to predict temperature, solid-state phase and residual stress fields for the multi-track multi-layer selective laser melting process of Ti6Al4V. The model considers the solid-state phase transformation (SSPT) and powder-liquid-solid transition which includes melting, vaporization, solidification, shrinkage and cooling phenomena. The thermal analysis is based on the transient heat conduction problem with a volumetric heat source describing the laser absorption and scattering in the powder bed. The volume fraction evolution of metallurgical phases is determined by temperature history and used to obtain the volumetric change strain due to the SSPT. An elasto-plastic constitutive law considering the strains that are induced by thermal gradients and the SSPT is proposed to evaluate stress fields. Modelling results reveal that the consideration of the SSPT leads to the decrease of tensile residual stresses and increase of compressive residual stresses, and the residual stress component in the scanning direction is larger than the other two stress components.